Unilateral radiotherapy treatment for p16/human papillomavirus–positive squamous cell carcinoma of unknown primary in the head and neck. (26th February 2018) - Tiong, Albert; Rischin, Danny; Young, Richard J.; Herschtal, Alan; Solomon, Ben; D'Costa, Ieta; Fua, Tsien; Liu, Chen; Coleman, Andrew; Kleid, Stephen; Dixon, Benjamin J.; Corry, June
Abstract : Objectives/Hypothesis: The outcomes of unilateral radiotherapy treatment for patients with p16/HPV‐positive squamous cell carcinomas of unknown primary (SCCUP) affecting cervical lymph nodes are under‐reported. Compared to radiating large volumes of the pharyngeal axis (the more common approach), this is potentially a much less toxic treatment for a good prognosis group. Study Design: Retrospective cohort study. Methods: We identified patients with SCCUP who were treated radically at our center and did not have parotid or isolated level IV or V nodal involvement. Failure‐free and overall survivals were calculated using Kaplan‐Meier methods. Results: From 2004 to 2012, there were 49 radically treated patients with SCCUP. Fourteen patients had bilateral neck treatment (they had bilateral nodal disease or suspected lesions in the base of tongue, though not proven with biopsy), two had surgery alone, whereas 33 had unilateral radiotherapy (after neck dissection, excisional biopsy, or definitively with concurrent chemotherapy). Of the 33 patients, 21 tested positive to p16/HPV and had median follow‐up of 57 months. In this group, no isolated contralateral neck failures or putative primaries emerged. There was 1/21 (4.3%) ipsilateral neck failure, 1/21 (4.3%) concurrent contralateral neck and distant failure, and 1/21 (4.3%) patient with distant failure. The 5‐year freedom from failure was 78% (95% confidence interval [CI]: 56%‐100%) and overall survival was 90% (95% CI: 79%‐100%). Conclusions: With no emergence of putative primaries and no isolated contralateral neck failures, this single‐institution experience in p16/HPV‐positive SCCUP patients suggests that unilateral radiotherapy may be an underutilized management strategy. Levels of Evidence: 4 Laryngoscope, 128:2076–2083, 2018